2017
DOI: 10.1101/166074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PI3Kδ inhibition supports memory T cells with enhanced antitumor fitness

Abstract: SUMMARYPhosphatidylinositol-3-kinase p110δ (PI3Kδ) inhibition by Idelalisib (CAL-101) in hematological malignancies directly induces apoptosis in cancer cells and disrupts immunological tolerance by depleting regulatory T cells (Tregs). Yet, little is known about the direct impact of PI3Kδ blockade on effector T cells from CAL-101 therapy. Herein, we demonstrate a direct effect of p110δ inactivation via CAL-101 on murine and human CD8+ T cells that promotes a strong undifferentiated memory phenotype (elevated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These cells exhibited a CD62L + early memory phenotype, suppressed glycolysis and superior anti-tumour efficacy [169]. Likewise, inhibiting the PI3Kδ catalytic subunit p110δ using the small molecule selective inhibitor Idelalisib (formerly CAL-101), can promote a strong undifferentiated memory phenotype in both murine and human CD8 + mesothelin-directed CAR T-cells (as well as pmel-1-directed transgenic TCR T-cells) characterized by the upregulation of transcription factor 7 (Tcf7) and elevated surface expression of CD62L, CCR7 and CD127 [170]. In vivo , Idelalisib-exposed CAR and transgenic TCR T-cells persisted longer following ACT and induced greater tumour regression compared to traditionally expanded CD8 + controls.…”
Section: Potential Strategies To Address Car Tonic Signallingmentioning
confidence: 99%
“…These cells exhibited a CD62L + early memory phenotype, suppressed glycolysis and superior anti-tumour efficacy [169]. Likewise, inhibiting the PI3Kδ catalytic subunit p110δ using the small molecule selective inhibitor Idelalisib (formerly CAL-101), can promote a strong undifferentiated memory phenotype in both murine and human CD8 + mesothelin-directed CAR T-cells (as well as pmel-1-directed transgenic TCR T-cells) characterized by the upregulation of transcription factor 7 (Tcf7) and elevated surface expression of CD62L, CCR7 and CD127 [170]. In vivo , Idelalisib-exposed CAR and transgenic TCR T-cells persisted longer following ACT and induced greater tumour regression compared to traditionally expanded CD8 + controls.…”
Section: Potential Strategies To Address Car Tonic Signallingmentioning
confidence: 99%
“…Previous research has shown that the PI3K inhibitor idelalisib can modulate T-cell differentiation in patients with B-cell NHL (130). Idelalisib also improved the persistence and antitumor function of adoptively transferred CD8 + T cells in vivo (131,132). On this basis, investigators have explored the use of PI3K inhibitors to induce a more favorable differentiation profile and enhance the antitumor function of CAR-T cells.…”
Section: Phosphoinositide 3-kinase Signaling Pathway Inhibitionmentioning
confidence: 99%